2022
DOI: 10.53730/ijhs.v6n3.12873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Konjac Glucomannan on indicators of metabolic syndrome in adults with schizophrenia

Abstract: Objectives: effects of konjac glucomannan (KGM) in adults with schizophrenia. Method post feasibility trial with 20 participants with elevated blood glucose, blood pressure, and triglycerides. Intervention konjac glucomannan for 1 to 1.5 h, 1 tablet times every day for 4 weeks, and were encouraged to practise the exercises at home. Main Outcome Measures Indicators of blood pressure, fasting blood glucose, triglycerides, and schizophrenia symptoms. Results: There was high acceptability and good adherence. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Some studies suggested that, given the same household resource endowment, the skill bias of migrant workers' identity significantly contributes to their return to entrepreneurship and employment, which can undoubtedly complement the human capital gap in rural development (Amarneh & Obeidat, 2022;Bindi et al, 2022;Mashudi et al, 2022). To sum up, it would be important to study the relationship between the degree of integration of the three industries as the dependent variable and the level of educational human capital as the independent variable, in order to further promote the integration of the three rural industries and the implementation of the rural revitalisation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that, given the same household resource endowment, the skill bias of migrant workers' identity significantly contributes to their return to entrepreneurship and employment, which can undoubtedly complement the human capital gap in rural development (Amarneh & Obeidat, 2022;Bindi et al, 2022;Mashudi et al, 2022). To sum up, it would be important to study the relationship between the degree of integration of the three industries as the dependent variable and the level of educational human capital as the independent variable, in order to further promote the integration of the three rural industries and the implementation of the rural revitalisation strategy.…”
Section: Introductionmentioning
confidence: 99%